Screening mammogram adherence in medically underserved women: Does language preference matter? - Vang, Suzanne (J Cancer Educ, 2022)
This study examines the relationship between language preference and screening mammogram adherence in medically underserved women in New York City. A survey was conducted with 518 women age 40 and over attending breast health education programs in English, Spanish, Chinese (Mandarin/Cantonese), and French. Women who preferred Chinese were 53% less likely to have had a mammogram within the past year compared to women who preferred English (p<.01). Women age 75 and older (p<.0001) and those without insurance (p<.05) were also found to be significantly less likely to have had a screening mammogram compared to women ages 55-74 and those with private insurance, respectively. This research indicates medically underserved women who prefer a non-English language may benefit from linguistically appropriate interventions to improve screening mammogram adherence. Future research should examine appropriateness of breast cancer screening for women age 75 and older and explore ways to improve screening mammogram use in the uninsured population.